JAWA DALAM PANDANGAN IMIGRAN JEPANG DI HINDIA BELANDA PADA AWAL ABAD KE-20 - Stedi Wardoyo (IZUMI, 2013)
ABSTRACT History of the relationship between Indonesia and Japan started with Japanese migration to Dutch`s East India (Indonesia) in the end of 19 century. At that time, Japanese did economic activities and made colonies not only in big cities such as Batavia (Jakarta), Medan and Surabaya but especially in Java which spread to small towns and villages. This paper will focus on the background of the Japanese migration to Java and Japanese migrants opinion about Java. The diary written by Okano Shigezo, one of the Japanese migrant at that time, used as main data sources beside the interview note with Kondo Sadaaki documented in Tokutei Kenkyuu Bunka Masatsu (Specific Research on Cultures) and stories of Japanese migrants life in Java before World War II as written in Jagatara Kanwa (Stories of Jakarta). Keywords: Japanese migrants, colony, opinion, Java, diary